Can family farmers thrive in commodity markets? Quantitative evidence on the heterogeneity in long agribusiness supply chains - Thiago de Carvalho Verano; Gabriel Medina; Jo\~ao Ricardo de Oliveira Júnior (Logistics, 2022)
Background: Family farmers' participation in marketing channels has prompted debates on the types of market best suited to this type of farmer. Commodity production by rural communities and the role of agribusiness long marketing channels for family-based farmers are the subjects of numerous qualitative studies. However, quantitative studies capable of assessing the relevance of long channels to family-based farmers are scarce. Therefore, this study intends to assess the relevance of long marketing channels for family farmers. Methods: We compiled the data from the survey responses of family farmers from 155 municipalities in a state in the central region of Brazil. Results: (1) There was an economic concentration of some marketing channels, namely, the sale of commodities occurred in 35% of the municipalities and included 4.15% of the sampled family farmers. The income derived through these channels represented 2.13% of the farmers' total income included in the study. (2) There is a low diversity of market types. On average, we found 2.95 long marketing channels per municipality. (3) Family farmers' participation is low in most commodity long channels. Between 0.11% and 4.15% of the family farmers in the sampled municipalities participate in these channels. Long channels linked to the cattle production chain showed more relevant capacity for inclusion. Conclusions: Contrary to the expectations of those behind initiatives to promote the marketing and sale of locally-sourced commodities within rural communities, agribusiness long marketing channels provide limited opportunities for family farmers to market their goods.
Keywords: 650; agri-food systems; agriculture; alternative models; Brazil; rural development